English language teachers’ perspectives on learner autonomy - Panta, Chetnath (Journal of NELTA, 2019)
This study explores the perceptions and practices of the English language teachers to create autonomous learning environment in the context of Nepalese secondary EFL classroom. The study further unpacks the role of the teachers in creating better learning opportunities for learners so as to promote learner autonomy. The research is based on interpretive paradigm to look into kaleidoscopic view of variety of perspectives, classroom practices and emerging dilemmas of the teachers. Based on the findings, the research showcases the deep rooted social practices and myths to bring tensions in the relation between teachers and students. The school environment has to be homely and autonomy supportive. It seems pertinent to think over the concept of learner autonomy globally and act locally adapting the global trends and issues of teaching and learning, and at the same time, there is a dire need to remain mindful of the translated concept of learner autonomy thinking contextually and pragmatically.